Towards more reliable measurements of sound absorption coefficient in reverberation rooms: An Inter-Laboratory Test. (August 2020) - Scrosati, Chiara; Martellotta, Francesco; Pompoli, Francesco; Schiavi, Alessandro; Prato, Andrea; D'Orazio, Dario; Garai, Massimo; Granzotto, Nicola; Di Bella, Antonino; Scamoni, Fabio; Depalma, Michele; Marescotti, Cristina; et al.
Abstract: The internationally recognized procedure ISO 354:2003 for measuring sound absorption coefficients under diffuse field conditions is now under revision. The main reason for this revision is the limited reproducibility of absorption coefficients measured in different laboratories that may have significant implications spanning from room acoustic design to material selection. A network of Italian laboratories have come together to carry out an Inter-Laboratory Test (ILT) to assess and compare the measurement uncertainties resulting from the application of the current version of ISO 354:2003 and of the new ISO/CD 354:2019. After detailing the methodological aspects, the paper presents the results of the measurements, discussing the compliance of the laboratories to the standard requirements and new qualification tests, and, more importantly, providing a quantitative estimation of their effects on measurement uncertainty and accuracy.